2022
DOI: 10.1039/d1fo03821d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polysaccharides from Tibetan turnip (Brassica rapaL.) on the gut microbiome afterin vitrofermentation andin vivometabolism

Abstract: Tibetan turnip ( Brassica rapa L. ) polysaccharide (TTP) is an active ingredient and has been studied for many years due to its biological effect. There are few studies on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The function of polysaccharides depends on their molecular weight and structure. According to our previous study, the Mw of TTP did not change significantly after gastrointestinal digestion, indicating that TTP was not easily degraded ( Liu et al, 2022 ). In the intestine, anaerobes use glucose (31.28%) and mannose (19.82%) in TTP to produce acetic acid.…”
Section: Discussionmentioning
confidence: 85%
“…The function of polysaccharides depends on their molecular weight and structure. According to our previous study, the Mw of TTP did not change significantly after gastrointestinal digestion, indicating that TTP was not easily degraded ( Liu et al, 2022 ). In the intestine, anaerobes use glucose (31.28%) and mannose (19.82%) in TTP to produce acetic acid.…”
Section: Discussionmentioning
confidence: 85%
“…We have discovered that Brassica rapa L. extract can optimize probiotics in vitro fermentation, suggesting its potential function in gut health [15]. These findings provide a theoretical basis for the deep investigation of the bioactive mechanism of Brassica rapa L. through its influence on the gut-muscle axis.…”
Section: Introductionmentioning
confidence: 79%
“…Research showed that the abundance of Firmicutes in obese patients was higher, while the abundance of Bacteroidetes was significantly lower than that in healthy people. Liu et al also found that the ratio of Firmicutes/Bacteroidetes in the gut microbiota of healthy people was high [21]. Previous studies have shown that the increase in Bacteroidetes was associated with overweight and obesity in pregnant women, which may increase the risk of intrauterine diseases in pregnant women [22,23].…”
Section: Changes In Community Structure and Compositionmentioning
confidence: 96%